The Effect of Implementing the Moodle-Based Ruangips.com Platform on Students’ Motivation and Social Studies Learning Outcomes in Grade XI at SMK Ar-Roudhoh Beji Pasuruan - Suhardi; Babul Bahrudin; Torkis Dalimunte (International Journal of Geography, Social, and Multicultural Education, 2026)
This study aims to analyze the effect of implementing Moodle-based ruangips.com platform on learning motivation and social studies learning outcomes of grade XI students at SMK Ar-Roudhoh Beji Pasuruan. This study employed a quantitative approach with a quasi-experimental pretest-posttest control group design. The population consisted of all 41 grade XI students divided into two classes: the Multimedia class (n=21) as the experimental group and the Computer and Network Engineering class (n=20) as the control group. Data were collected using a learning motivation questionnaire (30 items, α=0.89) and an achievement test (40 multiple-choice items, r₁₁=0.87). Data were analyzed using Independent Sample t-test and N-Gain analysis. Results showed: (1) there was a significant difference in learning motivation between experimental and control groups (t=4.712; p<0.05); (2) there was a significant difference in learning outcomes between the two groups (t=5.083; p<0.05); (3) the N-Gain of the experimental group was in the high category (g=0.72) while the control group was in the medium category (g=0.41). These findings imply that the Moodle-based ruangips.com platform is effective in improving IPS motivation and learning outcomes, and supports 21st century competency (4C) development in vocational students.